2020
DOI: 10.1097/md.0000000000018983
|View full text |Cite
|
Sign up to set email alerts
|

Occipitocervical fusion combined with 3-dimensional navigation and 3-dimensional printing technology for the treatment of atlantoaxial dislocation with basilar invagination

Abstract: Introduction: Basilar invagination (BI) is a common deformity in the occipitocervical region. The traditional surgical method of BI is direct transoral decompression followed by posterior decompression and fixation. Posterior-only decompression and fixation have achieved good efficacy in the treatment of BI in recent years, but complications are common due to the operation in the upper cervical vertebra and the medulla oblongata region. Moreover, posterior-only occipitocervical fusion combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…In a case report, the 3D printing technology can be applied to clarify the relationship between blood vessels and bone around the implant to minimize injury to important structures during implantation. [13] Based on our clinical experience, during MPFL reconstruction, the isometric point of the femoral tunnel (Schöttle point) varies due to individual development of the femur, so we verified that the use of 3D-printed individualized navigation template can solve some of the effects of individual differences, and at the same time can reduce the influence of the internal and external rotation of the femur on the positioning of the femoral tunnel during fluoroscopy. This study hypothesized that intraoperative use of the 3D-printed individualized navigation template technique to determine the Schöttle point for MPFL reconstruction compared with the fluoroscopic guidance technique would result in more accurate isometric points and better knee function in the early stages.…”
Section: This Study Was Funded By the National Natural Science Founda...supporting
confidence: 53%
See 1 more Smart Citation
“…In a case report, the 3D printing technology can be applied to clarify the relationship between blood vessels and bone around the implant to minimize injury to important structures during implantation. [13] Based on our clinical experience, during MPFL reconstruction, the isometric point of the femoral tunnel (Schöttle point) varies due to individual development of the femur, so we verified that the use of 3D-printed individualized navigation template can solve some of the effects of individual differences, and at the same time can reduce the influence of the internal and external rotation of the femur on the positioning of the femoral tunnel during fluoroscopy. This study hypothesized that intraoperative use of the 3D-printed individualized navigation template technique to determine the Schöttle point for MPFL reconstruction compared with the fluoroscopic guidance technique would result in more accurate isometric points and better knee function in the early stages.…”
Section: This Study Was Funded By the National Natural Science Founda...supporting
confidence: 53%
“…In a case report, the 3D printing technology can be applied to clarify the relationship between blood vessels and bone around the implant to minimize injury to important structures during implantation. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al . 15 used a 3D navigation system and 3D printing technology in a patient diagnosed with atlantoaxial dislocation and basilar invagination. The patient's walking disorder was resolved and he was able to walk approximately 100 m by himself with the help of a neck brace after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies have reported on ION for lumbar surgery, 1,6,[10][11][12][13][14][15][16][17] the use of ION for cervical spine surgery has largely been limited to the upper cervical spine, particularly for atlanto-occipital and C1-C2 surgery. [18][19][20][21][22] The few reports on ION for the lower cervical spine describe the use of this technology for posterior cervical foraminotomy (PCF) and report good clinical outcomes. [23][24][25] However, all these studies utilize bone-anchored trackers, such as a Mayfield clamp (Integra Life Sciences, Plainsboro, NJ) 23 or a dynamic reference base attached to the spinous process of vertebrae.…”
mentioning
confidence: 99%
“…Although numerous studies have reported on ION for lumbar surgery,1,6,10–17 the use of ION for cervical spine surgery has largely been limited to the upper cervical spine, particularly for atlanto-occipital and C1–C2 surgery 18–22. The few reports on ION for the lower cervical spine describe the use of this technology for posterior cervical foraminotomy (PCF) and report good clinical outcomes 23–25.…”
mentioning
confidence: 99%